miR-15a-3p Protects Against Isoniazid-Induced Liver Injury via Suppressing N-Acetyltransferase 2 Expression - Li, Xinmei; Zhang, Heng; Xu, Lin; Jin, Yuan; Luo, Jiao; Li, Chuanhai; Zhao, Kunming; Zheng, Yuxin; Yu, Dianke; Zhao, Yanjie (Frontiers in Molecular Biosciences, 2021)
Isoniazid (INH), an effective first-line drug for tuberculosis treatment, has been reported to be associated with hepatotoxicity for decades, but the underlying mechanisms are poorly understood. N-acetyltransferase 2 (NAT2) is a Phase II enzyme that specifically catalyzes the acetylation of INH, and NAT2 expression/activity play pivotal roles in INH metabolism, drug efficacy, and toxicity. In this study, we systematically investigated the regulatory roles of microRNA (miRNA) in NAT2 expression and INH-induced liver injury via a series of in silico, in vitro, and in vivo analyses. Four mature miRNAs, including hsa-miR-15a-3p, hsa-miR-628-5p, hsa-miR-1262, and hsa-miR-3132, were predicted to target the NAT2 transcript, and a negative correlation was observed between hsa-miR-15a-3p and NAT2 transcripts in liver samples. Further experiments serially revealed that hsa-miR-15a-3p was able to interact with the 3'-untranslated region (UTR) of NAT2 directly, suppressed the endogenous NAT2 expression, and then inhibited INH-induced NAT2 overexpression as well as INH-induced liver injury, both in liver cells and mouse model. In summary, our results identified hsa-miR-15a-3p as a novel epigenetic factor modulating NAT2 expression and as a protective module against INH-induced liver injury, and provided new clues to elucidate the epigenetic regulatory mechanisms concerning drug-induced liver injury (DILI).